Measuring counterparty risk in FMIs - Tatu Laine; Kasperi Korpinen (Bank of Finland, 2021)
This paper extends traditional payment system simulation analysis to counterparty liquidity risk exposures. The used stress test scenario corresponds to the counterparty stress scenario applied in the BCBS standard "Monitoring tools for intraday liquidity management" (BIS, 2013). This stress scenario is simulated for participants of the Finnish TARGET2 component with the new BoF-PSS3 simulator. Two liquidity deterioration indicators are introduced to quantify counterparty liquidity risk exposures. As comparison of liquidity risk projections to the available liquidity of participants in the system only yields a restricted and system-specific view of the severity of the scenarios, we compare the liquidity risks to high-quality liquid assets (HQLA) available at the group level to assess the overall liquidity risk that participants face in TARGET2. Our results generally comport with the literature and results reported elsewhere. Banking groups are exposed to a liquidity deterioration equivalent from 20 % to 60 % of their respective HQLA in just 0.35 % of the daily scenario observations. The exercise paper demonstrates that our proposed alternative form of payment system analysis can be helpful in banking supervision, micro- and macroprudential analysis, as well as resolution authorities' assessment of the effects of their actions on payment systems.
urn:nbn:fi:bof-202112152151
Keywords: 330; payment systems; stress testing; liquidity risks; counterparty risks; systemic risk; computer simulation